THE INFLUENCE OF CONSUMER PERCEPTION AND BRAND IMAGE ON CONSUMER LOYALTY THROUGH BRAND TRUST IN EIGER ADVENTURE FLAGSHIP STORE MAKASSAR - Asmiati (Scientium Management Review, 2022)
This study aims to determine the effect of consumer perceptions on product and brand image on consumer loyalty through brand trust at Eiger Adventure Flagship Store Makassar. This research is a quantitative research, the data used is primary data, namely data obtained from distributing questionnaires to research objects. The population in this study are consumers who have made purchases at the Eiger Adventure Flagship Store Makassar. The sampling technique used purposive sampling with a total sample of 150 respondents. The analytical method used in this study is regression analysis using the PLS (Partial Least Square) method with the help of SmartPLS 3.0 Software. The results showed that (1) consumer perceptions had a positive and significant effect on brand trust at the Eiger Adventure Flagship Store Makassar; (2) Brand image has a positive and significant effect on brand trust in the Eiger Adventure Flagship Store Makassar; (3) Consumer perceptions have no significant effect on consumer loyalty at the Eiger Adventure Flagship Store Makassar; (4) Brand image has a positive and significant effect on consumer loyalty at the Eiger Adventure Flagship Store Makassar; (5) Brand trust has a positive and significant effect on consumer loyalty at the Eiger Adventure Flagship Store Makassar; (6) Consumer perception has a significant effect on consumer loyalty through brand trust in Eiger Adventure Flagship Store Makassar;